PERBANDINGAN KINERJA REKSADANA SYARIAH DAN REKSADANA NON-SYARIAH DI INDONESIA BERDASARKAN RETURN, RESIKO, DAN KOEFISIEN VARIASI - Shafira Sa’adah Syauqiyah; Muhammad Nafik H. R (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research aims to find out the performance comparison between sharia mutual funds and non-sharia mutual funds in Indonesia during 2013-2015 by using return, risk, and coefficient of variation in the three types of mutual funds; equity mutual fund, mixed mutual fund, and fixed income mutual fund. The approach used is quantitative approach by using independent samples t-test or mann whitney in the test analysis with 5% significant level. The result of this study indicate that there is no significant difference between return, risk, and coefficient of variation of sharia mutual funds and non-sharia mutual funds in Indonesia in three types of mutual funds.  REFERENCESBrigham, Eugene dan Joel F. Houston. 2009. Fundamental of Financial Management 12th Edition. USA: South-Western Cengage LearningBursa Efek Indonesia. 2015. Sekolah Pasar Modal Syariah. JakartaHartono, Jogiyanto. 2012. Teori Portofolio dan Analisis Investasi. Yogyakarta: BPFE YogyakartaHirt, Geoffrey A. dan Stanley B. Block. 1999. Fundamentals of Investment Management. Singapore: McGraw-Hill Book Co.Huda, Nurul dan Mohamad Heykal. 2010. Lembaga Keuangan Islam. Jakarta: KencanaKandarisa, Nur Aini. 2014. Perkembangan dan Hambatan Reksadana Syariah di Indonesia: Suatu Kajian Teori. Jurnal Akuntansi Unesa Vol 2, No 2Karim, Adiwarman A. 2014. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: Raja Grafindo PersadaManan, Abdul. 2009. Aspek Hukum dalam Penyelenggaraan Investasi di Pasar Modal Syariah Indonesia. Jakarta: KencanaMasruroh, Aini. 2014. Konsep Dasar Investasi Reksadana. Jurnal Universitas Islam Negeri JakartaMelicher, Ronald D. dan Edgar A. Norton. 2003. Finance: Introduction to Institutions, Investment, and Management. USA: John Wiley & Sons, Inc.Ratnawati, Vince dan Ningrum Khairini. 2012. Perbandingan Kinerja Reksadana Syariah dan Reksadana Konvensional. Jurnal Akuntansi Vol 1, No 1Ryandono, M. Nafik Hadi. 2009. Bursa Efek dan Investasi Syariah. Jakarta: SerambiSudarsono, Heri. 2007. Bank dan Lembaga Keuangan Syariah. Yogyakarta: EkonisiaSuhartono dan Fadlillah Qudsi. 2009. Portofolio Investasi dan Bursa Efek. Yogyakarta: UPP STIM YKPNSutedi, Adrian. 2011. Pasar Modal Syariah. Jakarta: Sinar GrafikaTandelilin, Eduardus. 2010. Portofolio dan Investasi, Teori dan Aplikasi. Yogyakarta: KanisiusWahyudi, Imam dkk. 2013. Manajemen Risiko Bank Islam. Jakarta: Salemba Empat